Kemampuan Guru Menggunakan TIK Untuk Pengembangan di Taman Kanak-Kanak - febrialismanto febrialismanto; Hidayatun Nur (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2019)
The progress of the era is recognised by the development of Technology and Information. Almost everyone uses technology and information in their lives. The use of Technology and Information has entered the world of education. The teacher has a big role to use technology and information in learning. The purpose of this study was to determine the ability of teachers to use ICTs for development in kindergartens, Riau Province. In kindergarten there is a development that should get attention in learning that is cognitive, language, physical, social & emotional, religious & moral values, and art. From the research results, it can be seen that teachers use Technology and Information for development is still low. Besides that the use of ICTs makes teaching materials, change learning, store materials and learning outcomes, communicate learning materials and results, and disseminate information on materials and learning outcomes of teachers are categorized into the low category.Kemajuan zaman ditandai dari berkembangnya kemajuan dalam Teknologi dan Informasi. Hampir semua orang menggunakan Teknologi dan informasi dalam semua pada saat ini dalam kehidupannya. Penggunaan Teknologi dan Informasi sudah masuk dalam dunia pendidikan. Guru memiliki peran yang besar memanfaatkan teknologi dan informasi dalam pembelajaran. Tujuan penelitian ini untuk mengetahui kemampauan guru menggunakan TIK untuk pengembangan di Taman Kanak-Kanak di Provinsi Riau. Di Taman Kanak-kanak ada pengembangan yang harus mendapatkan perhatian dalam pembelajaran yaitu kognitif, bahasa, fisik motorik, sosial & emosional, nilai agama & moral, dan seni. Dari hasil penelitian dapat diketahui guru menggunakan Teknologi dan Informasi untuk pengembangan masih rendah. Disamping itu Penggunaan TIK membuat bahan ajar, mengubah pembelajaran, menyimpan bahan dan hasil pembelajaran, mengkomunikasikan bahan dan hasil pembelajaran, serta menyebarkan informasi bahan dan hasil pembelajaran guru termasuk dalam kategori rendah.